2019
DOI: 10.1002/dev.21841
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic regulation of preterm infants is enhanced by Family Nurture Intervention

Abstract: Preterm infants have maturational delays in several neurobehavioral systems. This study assesses the impact of the Family Nurture Intervention (FNI) in the neonatal intensive care unit (NICU) on the maturation of autonomic regulation of preterm infants. Preterm infants born at 26–34 weeks postmenstrual age (PMA) were assigned to groups receiving either standard care (SC) or SC plus FNI, using a randomized controlled trial design. At two collection time points, approximately 35 weeks and 41 weeks PMA, electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 46 publications
1
61
0
1
Order By: Relevance
“…Children who receive this intervention also exhibit higher cardiac VVC regulation (measured by RSA), attenuated stress response, better cognitive control, and better organized sleep through the first 10 years of life (Feldman, Rosenthal, & Eidelman, ). The Family Nurture Intervention, a psychosocial intervention based on Calming Cycle Theory that promotes mother‐infant emotional connection through direct interpersonal communication of affect (Welch, ) has also shown promise in preterm infants, with benefits for VVC regulation, socioemotional function, and neurodevelopmental outcomes (Porges et al, in press; Welch et al, ). Interventions focused on parent–child interactions may also improve autonomic function in older children (e.g., Hastings et al, ).…”
Section: An Autonomic State Regulation Perspective On Treatment and Pmentioning
confidence: 99%
“…Children who receive this intervention also exhibit higher cardiac VVC regulation (measured by RSA), attenuated stress response, better cognitive control, and better organized sleep through the first 10 years of life (Feldman, Rosenthal, & Eidelman, ). The Family Nurture Intervention, a psychosocial intervention based on Calming Cycle Theory that promotes mother‐infant emotional connection through direct interpersonal communication of affect (Welch, ) has also shown promise in preterm infants, with benefits for VVC regulation, socioemotional function, and neurodevelopmental outcomes (Porges et al, in press; Welch et al, ). Interventions focused on parent–child interactions may also improve autonomic function in older children (e.g., Hastings et al, ).…”
Section: An Autonomic State Regulation Perspective On Treatment and Pmentioning
confidence: 99%
“…Integrating awareness of arousal regulation with sensorimotor-based treatments are necessary, including a promising trend towards decreasing EDA magnitude (e.g., Miller et al, 2007;Bodison and Parham, 2018;Foitzik and Brown, 2018). Sensorimotor-focused treatment strategies can impact a variety of distributed properties and benefit from being coupled with socio-emotional and play-based relational approaches (Greenspan et al, 1998;Bundy et al, 2008;Lillas et al, 2018;Pfeiffer et al, 2018;Roberts et al, 2018;Schaaf et al, 2018;Delahooke, 2019;Porges et al, 2019). This integrated, interdisciplinary lens better addresses sensorimotor over-and under-responsivity in tandem with the arousal and emotional dysregulation related to internal stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…Columbia is focused on the restorative nature of emotional connection. The Family Nurture Intervention (FNI) trials have shown dramatic and impressive benefits from an intervention that started an average of 7 days following preterm birth, despite protocol designed to begin FNI as soon as possible after birth (Porges et al, ; Welch et al, ; Welch et al, ; Welch & Myers, ). Columbia NSP is testing the hypothesis that it is not too late to reestablish the healing powers of emotional connection in children 0–5 years of age.…”
Section: Critical Periodmentioning
confidence: 99%
“…Calming cycle theory describes the process by which an emotional connection and autonomic coregulation can be reestablished between mother and infant utilizing the natural learning mechanism that makes it possible for the two to connect upon birth. Calming cycle theory extends polyvagal theory by providing a learning mechanism by which the vagus nerve controls heart rate and vagal tone (Ludwig & Welch, ; Porges et al, ). It proposes that an association is formed between the autonomic states of infant and mother during gestation via Pavlovian coconditioning (autonomic learning), which leads to a cardiac calming reflex and emotional connection following normal birth (Welch & Ludwig, ).…”
Section: Calming Cycle Theorymentioning
confidence: 99%